Dental biofilm and saliva microbiome and its interplay with pediatric allergies - Arweiler, Nicole; Rahmel, Vivien; Alashkar Alhamwe, Bilal; Alhamdan, Fahd; Zemlin, Michael; Boutin, Sébastien; Dalpke, Alexander; Renz, Harald (Microorganisms, 2021)
Little is known about the interplay and contribution of oral microorganisms to allergic diseases, especially in children. The aim of the clinical study was to associate saliva and dental biofilm microbiome with allergic disease, in particular with allergic asthma. In a single-center study, allergic/asthmatic children (n = 15; AA-Chd; age 10.7 ± 2.9), atopic/allergic children (n = 16; AT/AL-Chd; 11.3 ± 2.9), and healthy controls (n = 15; CON-Chd; age 9.9 ± 2.2) were recruited. After removing adhering biofilms from teeth and collecting saliva, microbiome was analyzed by using a 16s-rRNA gene-based next-generation sequencing in these two mediums. Microbiome structure differed significantly between saliva and dental biofilms (β-diversity). Within the groups, the dental biofilm microbiome of AA-Chd and AT/AL-Chd showed a similar microbial fingerprint characterized by only a small number of taxa that were enriched or depleted (4) compared to the CON-Chd, while both diseased groups showed a stronger microbial shift compared to CON-Chd, revealing 14 taxa in AA-Chd and 15 taxa in AT/AL-Chd that were different. This could be the first note to the contribution of dental biofilm and its metabolic activity to allergic health or disease.